Hubungan Usia dan Gravida dengan Kejadian Kek pada Ibu Hamil di Wilayah Kerja Puskesmas Wonosegoro - Sri Sulistiyani; Luluk Khusnul Dwihestie; Yanti Yanti (Universitas Nurul Jadid, 2026)
Chronic Energy Deficiency (CED) among pregnant women is influenced by direct factors, such as nutritional intake and infectious diseases, as well as indirect factors, including age, parity, education, employment, economic status, knowledge, and access to health services. Preliminary data from the Wonosegoro Community Health Center in 2025 showed a high number of CED cases among pregnant women, with 81 recorded cases. This study aimed to analyze the relationship between age and parity and the incidence of CED among pregnant women in the Wonosegoro Community Health Center service area. This research used a quantitative method with an analytical survey approach and a retrospective case-control design. The sample consisted of 81 pregnant women with CED as the case group and 81 pregnant women without CED as the control group. Data were obtained from medical records and analyzed using Fisher’s Exact Test. The results showed that most respondents were in the low-risk age group of 20–35 years, totaling 132 respondents (81.5%), and in the low-risk parity group of 1–3, totaling 151 respondents (93.2%). The analysis showed a significant relationship between age and CED incidence with a p-value of 0.025, and between parity and CED incidence with a p-value of 0.009. The odds ratio for age was 2.800, while the odds ratio for parity was 11.268. Therefore, age and parity were associated with CED incidence among pregnant women. These findings may serve as input for health workers to improve education on CED prevention before pregnancy.